DINAMIKA PERAN POLITIK TUAN GURU DI LOMBOK ERA REFORMASI - Muh. Samsul Anwar (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2017)
Regional autonomy implementations have implications for local politic expression. Political actor and community participation in local politic increase, emerge local politic actors, and local politic culture that it play the role of local politics, such as “Tuan Guru” (teacher) in Lombok. Tuan Guru has the more prominent role from the others inside Lombok local politics.There are three kind of Tuan Guru who are involved in practical politics; first, a Tuan Guru who politician that he is focuses his activity in the practical politics. His political activity is more dominant than teach about religion to the pupils (jamaah) or the rasta (santri). Second, Tuan Guru who involve in the pratical politics, but only to be a vote gather. This one thought himself doesn’t has politic capacity, especially political politics. Some people as a vote gather gain aid for his “pesantren” (boarding school) and “madrasah” (school). He prefer to teach about religion for the pupils than do pratical politics activity. Third, Tuan Guru who doesn’t take part of politics. Tuan Guru focus on religion to keep his peace of soul, statics, and conservative. He prefer oriented for the akhirat’s life (dooms day), so he looks closed from outsider dynamic inside to determine politic affiliation